Penerapan Konsep âWelcome to Malangâ Pada Desain Interior Perpustakaan Umum dan Arsip Kota Malang - Japutra, Irene Nathania (Intra, 2014)
Public Library and Archive of Malang is a library that managed by the city government. The library financed by government for library development. The development of the library collection has been done and needs further development on its interior design. This development aims to fix the library interior in order to support the library system and make it more comfortable and interesting. The library is expected to become an icon of Malangâs education. This expectation then bodied in the library re-design theme, called